Short and Long-Term Relationships among the Surety Bond Market, the Building Sector, and Relevant Nominal Variables Related to the Construction Industry: The Mexican Case (2006-2014) - Alejo-GarcÃa, Marco Antonio; Venegas-MartÃnez, Francisco; Cruz-Aké, Salvador (International Journal of Economics and Financial Issues, 2017)
This paper is aimed at examining the relationship among the surety bond market, the building sector, and several important nominal variables related to the construction industry en México during 2006-2014. To do this, we use Vector Autoregressive (VAR) and cointegration models in order to find short- and long-run relationships. We also perform a Granger causality analysis and an impulse-response examination, as well as variance decomposition. The main finding is that the surety industry responds to changes in: GDP from construction, credits for the construction sector, revenues of the private construction, and credit defaults. We also find empirical evidence that in the long run the surety industry reacts to: the government investment, the default in this industry, and the interest rate. Keywords: surety markets, building sector, nominal variables, time series analysis. JEL Classifications: G22, E44, C32.